Prevention of salmonella infection by contact using intestinal flora of adult birds and/or a mixture of organic acids - De Oliveira, Gláucia Helaine [UNESP]; Berchieri Jr., Angelo [UNESP]; Barrow, Paul A. (My University, 2000)
This study was carried out to assess the ability of competitive exclusion and a mixture of organic acids to prevent Salmonella infection by contact between newly hatched chicks. A bird infected with Salmonella was placed in a box containing non-infected birds, previously treated with a broth culture of faeces of adult birds (CE) and/or a mixture of organic acids. The number of Salmonella organisms in the caeca of the contact birds was estimated at 4 and 8 days post-challenge. The birds were infected with Salmonella Typhimurium, Salmonella Enteritidis (both repeated 5 times), Salmonella Agona and Salmonella Infantis (3 repetitions). The same approach was used to test the mixture of organic acids alone. In this case the birds received feed containing 0.8% of a mixture of formic acid (70%) and propionic acid (30%). Also, a third trial was carried out with birds inoculated with the broth culture of faeces and fed with feed containing the mixture of organic acids. Appropriate controls were included. Whereas the birds from the control groups and the groups treated with the mixture of organic acids were heavily infected with Salmonella, those pre-treated with CE or CE plus the mixture of organic acids had no viable cells per gram of caecal contents.
Keywords: By-contact infection; Competitive exclusion; Organic acids; Poultry; Salmonella